Analisis Faktor Usia, Pendidikan dan Pekerjaan Ibu terhadap Tingkat Pengetahuan Ibu Balita Stunting tentang Perilaku Hidup Bersih dan Sehat di Kabupaten Balangan - Salman, Yuliana; Risnawati, Risnawati; Perdani, Rizki; Husin, Husin; Hamdie, Zuraida Murdia (HB PRESS, 2024)
Based on the results of the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting in South Kalimantan is 30% above the national figure, namely 24.4%. One of the factors causing stunting is infectious diseases such as diarrhea, worms, and tuberculosis. These infectious diseases are closely related to healthy lifestyles which are reflected in Clean and Healthy Living Behavior (PHBS) in the Household. Factors that influence the implementation of PHBS include age, education, employment and mother's knowledge, so it is necessary to study the relationship between these factors in order to create a healthy lifestyle in the family environment. This research uses an analytical survey method with a cross sectional design. The population of this study was mothers who had stunted toddlers in 34 villages in Balangan Regency, totaling 379 respondents. The sampling technique uses total sampling. The research instrument was a questionnaire on the mother's identity and knowledge about PHBS. Data analysis used the chi-square test. The results of the study showed that the majority of stunting mothers of toddlers were in the age range 20 - 40 years, namely 328 respondents (85.5%), the highest level of education was secondary education at 222 respondents (58.6%), the majority of respondents did not work as many as 258 respondents (68.1%) and the level of knowledge of respondents about PHBS mostly had knowledge in the good category, namely 255 respondents (67.3%). Conclusion of this study there is a relationship between mother's occupation and mother's knowledge.